FORUM: Ecological networks: the missing links in biomonitoring science. Issue 5 (28th July 2014) - Gray, Clare; Baird, Donald J.; Baumgartner, Simone; Jacob, Ute; Jenkins, Gareth B.; O'Gorman, Eoin J.; Lu, Xueke; Ma, Athen; Pocock, Michael J. O.; Schuwirth, Nele; Thompson, Murray; Woodward, Guy; et al.
Summary Monitoring anthropogenic impacts is essential for managing and conserving ecosystems, yet current biomonitoring approaches lack the tools required to deal with the effects of stressors on species and their interactions in complex natural systems. Ecological networks (trophic or mutualistic) can offer new insights into ecosystem degradation, adding value to current taxonomically constrained schemes. We highlight some examples to show how new network approaches can be used to interpret ecological responses. Synthesis and applications. Augmenting routine biomonitoring data with interaction data derived from the literature, complemented with ground‐truthed data from direct observations where feasible, allows us to begin to characterise large numbers of ecological networks across environmental gradients. This process can be accelerated by adopting emerging technologies and novel analytical approaches, enabling biomonitoring to move beyond simple pass/fail schemes and to address the many ecological responses that can only be understood from a network‐based perspective.